AB0562 A double-blind, placebo-controlled, multicenter trial of tocilizumab in moderate to severe active RA patients with inadequate response to methotrexate in korean population. (23rd January 2014) - Lim, M.J.; Park, S.H.; Shim, S.-C.; Baek, H.J.; Yoo, D.-H.; Kim, H.A.; Lee, S.K.; Lee, Y.J.; Park, Y.E.; Cha, H.-S.; Park, W.; Song, Y.-W.
Abstract : Background: Interleukin-6 (IL-6), a proinflammatory cytokine, is thought to play a major pathological role in rheumatoid arthritis (RA). Tocilizumab is humanized anti IL-6 receptor monoclonal antibody which has been shown to improve signs and symptoms of RA. Objectives: To investigate the efficacy and safety of tocilizumab in a Korean population. Methods: This clinical trial was a 24-week phase III, randomized, double-blind, placebo-controlled, multicenter trial with two treatments arms and conducted from October, 2009 to October, 2010. The eligible patients had moderate to severe active RA, inadequately responding to MTX (or DMARDs). Tocilizumab at a dose of 8mg/kg or placebo were administered in a blinded manner, intravenously every 4 weeks, with stable dose of methotrexate (MTX) or other DMARDs. Results: Total of 80 patients completed 24 week's treatment with 40 patients in each treatment arm. At week 24, proportions of ACR 20, ACR 50, DAS28 remission and EULAR response were significantly higher in Tocilizumab group than in placebo group ( p <0.0001, p =0.0002, p =0.0002 and p <0.0001, respectively as shown in Table 1 ). The mean hemoglobin level was increased and the rheumatoid factor titer was decreased in Tocilizumab group, compared to those of placebo group ( p =0.0002, p =0.0055, respectively). Adverse drug reactions were more frequent in Tocilizumab group than in placebo group as follows; increased SGPT (21%), granulocytopenia (17%), leukocytopenia (15%), hypercholesterolemia (13%), pharyngitis (13%), and increased SGOT (10%). There were more incidences of serious adverse drug reactions in Tocilizumab group than in placebo group, but it was not significant ( p =0.0548). Conclusions: In Korean population, administration of tocilizumab 8 mg/kg in combination with MTX (with or without other DMARDs) reduced RA activity significantly. Most of RA activity parameters including ACR 20, ACR 50, DAS 28 remission and EULAR response were achieved more frequently in Tocilizumab group than in placebo group. Tocilizumab was generally well tolerated since no safety issue was observed during the study. This study was financially supported by JW Pharmaceutical Co. (KFDA clinical trial-146). References: Maini RN, et al. Arthritis Rheum. 2006;54(9):2817-29. Jones G, et al. Ann Rheum Dis. 2010;69(1):88-96. Disclosure of Interest: None Declared